(3JhVjM GdecGSHs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg(B: (3hGdSfI GdeJhGJQI, bGd UGMH eaJGM GdcQGeI hCeG GdCNHGQ aEfgG bO JRjO Ydi GdNeSI YTQ hcdgG JVefJ JMQje GddYH Pdc hGdCcd efgs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg hdG aj GfaGP hUGjG Cf dG jaQbhf GdfGS Hjf eG fMf ajg hHjf GdOjhf GddJj Ydi GdXdeI aj YOe GNQGLgG ef JQcI GdXGde bHd JfajP GdhUjI hGdejQGKs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis